2002
DOI: 10.1007/s00330-002-1333-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI in diffuse axonal injury of the brain

Abstract: The goal of this study was to identify and describe the different types and patterns of tissue injury which are encountered by diffusion-weighted imaging (DWI) in diffuse axonal injury (DAI) of the brain. The DWI data sets of 98 patients who suffered from a closed-head injury were retrospectively evaluated. Medical records were reviewed to rule out pre-existing neurological diseases. Lesions were studied for their DWI signal characteristics and lesion size or extension. Traumatic lesions were classified into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 16 publications
0
61
1
Order By: Relevance
“…This indicates that the type of microstructural change was different in both locations. The ADC increase in the genu may imply a larger contribution of vasogenic edema 23 in this location than in the splenium. Conventional imaging and pathologic-anatomic study have indicated that the posterior corpus callosum is more susceptible to fiber disruption than the anterior corpus callosum.…”
Section: Discussionmentioning
confidence: 93%
“…This indicates that the type of microstructural change was different in both locations. The ADC increase in the genu may imply a larger contribution of vasogenic edema 23 in this location than in the splenium. Conventional imaging and pathologic-anatomic study have indicated that the posterior corpus callosum is more susceptible to fiber disruption than the anterior corpus callosum.…”
Section: Discussionmentioning
confidence: 93%
“…The typical diffusion times used for clinical DWI are 10 -50 ms, corresponding to average molecular displacements on the order of 10 m. This microscopic spatial scale is in the same range as that of cellular dimensions. This sensitivity to cellular processes has been exploited clinically for improving the detection of acute cerebral ischemia, 4,6-10 distinguishing vasogenic from cytotoxic edema, [11][12][13][14][15][16] identifying foci of axonal shearing injury after acute head trauma, [17][18][19] characterizing cellularity in brain tumors, [20][21][22][23][24][25][26][27] discriminating between metastases and gliomas 22,27 and between tumor recurrence and postsurgical injury, 28 differentiating pyogenic abscesses from tumors, [29][30][31] and for the noninvasive mapping of white matter connectivity by using the diffusion tensor model, [32][33][34][35][36] among other applications.…”
Section: Theoretic Underpinnings Of Diffusion Imagingmentioning
confidence: 99%
“…In analogy to stroke-related brain injury, DWI is increasingly investigated for its value in the evaluation of traumatic brain injury [47]. Especially in the evaluation of diffuse axonal injury (DAI), DWI may prove to be valuable (Figs.…”
Section: Clinical Application Of Diffusion-weighted Mrimentioning
confidence: 99%